The Shedding of Membrane-anchored Heparin-binding Epidermal-like Growth Factor Is Regulated by the Raf/Mitogen-activated Protein Kinase Cascade and by Cell Adhesion and Spreading - Ze’ev Gechtman; José Luís Izquierdo Alonso; Gerhard Raab; Donald E. Ingber; Michael Klagsbrun (1999)
Heparin-binding epidermal-like growth factor (HB-EGF) is synthesized as a transmembrane precursor (HB-EGFTM). The addition of phorbol ester (PMA, phorbol 12-myristate 13-acetate) to cells expressing HB-EGFTM results in the metalloproteinase-dependent release (shedding) of soluble HB-EGF. To analyze mechanisms that regulate HB-EGF shedding, a stable cell line was established expressing HB-EGFTM in which the ectodomain and the cytoplasmic tail were tagged with hemagglutinin (HA) and Myc epitopes, respectively (HB-EGFTMHA/Myc). HB-EGFTMHA/Myc cleavage was followed by the appearance of soluble HB-EGFHA in conditioned medium, the loss of biotinylated cell-surface HB-EGFTMHA/Myc, and the appearance of a Myc-tagged cytoplasmic tail fragment in cell lysates. By using this approach, several novel metalloproteinase-dependent regulators of HB-EGFTM shedding were identified as follows. (i) HB-EGFTMHA/Myc shedding induced by PMA was blocked by the mitogen-activated protein (MAP) kinase kinase inhibitor, PD98059. PMA activated MAP kinase within 5 min, but HB-EGFTMHA/Myc shedding did not occur until 20 min, suggesting that MAP kinase activation was a necessary step in the pathway of PMA-induced HB-EGFTM cleavage. (ii) Activation of an inducible Raf-1 kinase, ΔRaf-1:estrogen receptor, resulted in a rapid MAP kinase activation within 10 min and shedding of HB-EGFTMHA/Myc within 20–40 min. (iii) Serum induced MAP kinase activation and HB-EGFTMHA/Myc shedding that were inhibited by PD98059. (iv) Whereas PMA induced HB-EGFTMHA/Myc shedding in attached cells, no shedding occurred when the cells were placed in suspension. Shedding was fully restored shortly after cells were allowed to spread on fibronectin, and the extent of PMA-induced shedding increased with the extent of cell spreading. PMA induced the same level of MAP kinase activation whether the cells were attached or in suspension suggesting that although MAP kinase activation might be necessary for shedding, it was not sufficient. Taken together, these results suggest that there are two components of cell regulation that contribute to the shedding process, not previously recognized, the Raf-1/MAP kinase signal transduction pathway and cell adhesion and spreading. Heparin-binding epidermal-like growth factor (HB-EGF) is synthesized as a transmembrane precursor (HB-EGFTM). The addition of phorbol ester (PMA, phorbol 12-myristate 13-acetate) to cells expressing HB-EGFTM results in the metalloproteinase-dependent release (shedding) of soluble HB-EGF. To analyze mechanisms that regulate HB-EGF shedding, a stable cell line was established expressing HB-EGFTM in which the ectodomain and the cytoplasmic tail were tagged with hemagglutinin (HA) and Myc epitopes, respectively (HB-EGFTMHA/Myc). HB-EGFTMHA/Myc cleavage was followed by the appearance of soluble HB-EGFHA in conditioned medium, the loss of biotinylated cell-surface HB-EGFTMHA/Myc, and the appearance of a Myc-tagged cytoplasmic tail fragment in cell lysates. By using this approach, several novel metalloproteinase-dependent regulators of HB-EGFTM shedding were identified as follows. (i) HB-EGFTMHA/Myc shedding induced by PMA was blocked by the mitogen-activated protein (MAP) kinase kinase inhibitor, PD98059. PMA activated MAP kinase within 5 min, but HB-EGFTMHA/Myc shedding did not occur until 20 min, suggesting that MAP kinase activation was a necessary step in the pathway of PMA-induced HB-EGFTM cleavage. (ii) Activation of an inducible Raf-1 kinase, ΔRaf-1:estrogen receptor, resulted in a rapid MAP kinase activation within 10 min and shedding of HB-EGFTMHA/Myc within 20–40 min. (iii) Serum induced MAP kinase activation and HB-EGFTMHA/Myc shedding that were inhibited by PD98059. (iv) Whereas PMA induced HB-EGFTMHA/Myc shedding in attached cells, no shedding occurred when the cells were placed in suspension. Shedding was fully restored shortly after cells were allowed to spread on fibronectin, and the extent of PMA-induced shedding increased with the extent of cell spreading. PMA induced the same level of MAP kinase activation whether the cells were attached or in suspension suggesting that although MAP kinase activation might be necessary for shedding, it was not sufficient. Taken together, these results suggest that there are two components of cell regulation that contribute to the shedding process, not previously recognized, the Raf-1/MAP kinase signal transduction pathway and cell adhesion and spreading. The extracellular domains of many membrane-anchored proteins are proteolytically cleaved from the cell surface in a process termed as shedding. Shedding is an irreversible post-translational modification that regulates biological function by releasing growth factors, enzymes, and soluble receptors (1Bosenberg M.W. Massague J. Curr. Opin. Cell Biol. 1993; 5: 832-838Crossref PubMed Scopus (66) Google Scholar, 2Blobel C.P. Cell. 1997; 90: 589-592Abstract Full Text Full Text PDF PubMed Scopus (330) Google Scholar, 3Werb Z. Yan Y. Science. 1998; 282: 1279-1280Crossref PubMed Google Scholar). For example, shedding converts a juxtacrine growth factor such as the membrane-anchored TGF-α 1The abbreviations used are:TGF-αtransforming growth factor-αTNF-αtumor necrosis factor-αHB-EGFheparin-binding EGF-like growth factorEGFepidermal growth factorPMAphorbol 12-myristate 13-acetateMAP kinasemitogen-activated protein kinaseERKextracellular signal-regulated kinaseMDC9metalloproteinase/disintegrin/cysteine-rich protein 9ADAMadisintegrinand metalloproteinaseβ-APPβ-amyloid precursor proteinα-MEMα-minimal essential mediumCHOChinese hamster ovaryHAhemagglutininCMconditioned mediumMEKMAP kinase/ERKPBSphosphate-buffered salineBSAbovine serum albuminERestrogen receptorCAPS3-(cyclohexylamino)propanesulfonic acidCHAPS3-[(3-cholamidopropyl)dimethylammonio]-1-propanesulfonic acid 1The abbreviations used are:TGF-αtransforming growth factor-αTNF-αtumor necrosis factor-αHB-EGFheparin-binding EGF-like growth factorEGFepidermal growth factorPMAphorbol 12-myristate 13-acetateMAP kinasemitogen-activated protein kinaseERKextracellular signal-regulated kinaseMDC9metalloproteinase/disintegrin/cysteine-rich protein 9ADAMadisintegrinand metalloproteinaseβ-APPβ-amyloid precursor proteinα-MEMα-minimal essential mediumCHOChinese hamster ovaryHAhemagglutininCMconditioned mediumMEKMAP kinase/ERKPBSphosphate-buffered salineBSAbovine serum albuminERestrogen receptorCAPS3-(cyclohexylamino)propanesulfonic acidCHAPS3-[(3-cholamidopropyl)dimethylammonio]-1-propanesulfonic acid precursor into a potent paracrine growth factor (4Brachmann R. Lindquist P.B. Nagashima M. Kohr W. Lipari T. Napier M. Derynck R. Cell. 1989; 56: 691-700Abstract Full Text PDF PubMed Scopus (340) Google Scholar, 5Wong S.T. Winchell L.F. McCune B.K. Earp H.S. Teixido J. Massague J. Herman B. Lee D.C. Cell. 1989; 56: 495-506Abstract Full Text PDF PubMed Scopus (375) Google Scholar, 6Arribas J. Massague J. J. Cell Biol. 1995; 128: 433-441Crossref PubMed Scopus (130) Google Scholar). Phorbol esters, such as PMA, are among the best characterized inducers of shedding. PMA treatment of cells results in metalloproteinase-dependent proteolytic cleavage of cell-surface-anchored precursors such as TGF-α, β-APP (6Arribas J. Massague J. J. Cell Biol. 1995; 128: 433-441Crossref PubMed Scopus (130) Google Scholar), and TNF-α (7Pradines F.A. Raetz C.R. J. Biol. Chem. 1992; 267: 23261-23268Abstract Full Text PDF PubMed Google Scholar). The PMA-induced shedding of TGF-α has been well characterized (8Pandiella A. Massague J. J. Biol. Chem. 1991; 266: 5769-5773Abstract Full Text PDF PubMed Google Scholar). It has been suggested that all the components required for TGF-α shedding are located at or close to the cell surface (9Bosenberg M.W. Pandiella A. Massague J. J. Cell Biol. 1993; 122: 95-101Crossref PubMed Scopus (54) Google Scholar). There may be a common mechanism for PMA-induced shedding since a mutant CHO cell line isolated for its inability to cleave TGF-α was unable to cleave β-APP and a variety of other cell-surface molecules in response to PMA (6Arribas J. Massague J. J. Cell Biol. 1995; 128: 433-441Crossref PubMed Scopus (130) Google Scholar). transforming growth factor-α tumor necrosis factor-α heparin-binding EGF-like growth factor epidermal growth factor phorbol 12-myristate 13-acetate mitogen-activated protein kinase extracellular signal-regulated kinase metalloproteinase/disintegrin/cysteine-rich protein 9 adisintegrinand metalloproteinase β-amyloid precursor protein α-minimal essential medium Chinese hamster ovary hemagglutinin conditioned medium MAP kinase/ERK phosphate-buffered saline bovine serum albumin estrogen receptor 3-(cyclohexylamino)propanesulfonic acid 3-[(3-cholamidopropyl)dimethylammonio]-1-propanesulfonic acid transforming growth factor-α tumor necrosis factor-α heparin-binding EGF-like growth factor epidermal growth factor phorbol 12-myristate 13-acetate mitogen-activated protein kinase extracellular signal-regulated kinase metalloproteinase/disintegrin/cysteine-rich protein 9 adisintegrinand metalloproteinase β-amyloid precursor protein α-minimal essential medium Chinese hamster ovary hemagglutinin conditioned medium MAP kinase/ERK phosphate-buffered saline bovine serum albumin estrogen receptor 3-(cyclohexylamino)propanesulfonic acid 3-[(3-cholamidopropyl)dimethylammonio]-1-propanesulfonic acid In PMA-induced shedding, the enzymes responsible for proteolytic cleavage and release appear to be metalloproteinases since shedding is blocked by synthetic hydroxamic acid-based compounds that are metalloproteinase inhibitors (10Mullberg J. Durie F.H. Otten-Evans C. Alderson M.R. Rose-John S. Cosman D. Black R.A. Mohler K.M. J. Immunol. 1995; 155: 5198-5205PubMed Google Scholar, 11Crowe P.D. Walter B.N. Mohler K.M. Otten E.C. Black R.A. Ware C.F. J. Exp. Med. 1995; 181: 1205-1210Crossref PubMed Scopus (245) Google Scholar, 12Preece G. Murphy G. Ager A. J. Biol. Chem. 1996; 271: 11634-11640Abstract Full Text Full Text PDF PubMed Scopus (192) Google Scholar, 13Feehan C. Darlak K. Kahn J. Walcheck B. Spatola A.F. Kishimoto T.K. J. Biol. Chem. 1996; 271: 7019-7024Abstract Full Text Full Text PDF PubMed Scopus (130) Google Scholar, 14Arribas J. Coodly L. Vollmer P. Kishimoto T.K. Rose-John S. Massague J. J. Biol. Chem. 1996; 271: 11376-11382Abstract Full Text Full Text PDF PubMed Scopus (359) Google Scholar, 15Suzuki M. Raab G. Moses M.A. Fernandez C.A. Klagsbrun M. J. Biol. Chem. 1997; 272: 31730-31737Abstract Full Text Full Text PDF PubMed Scopus (270) Google Scholar). Among the metalloproteinases, the disintegrin metalloproteinases known as ADAMs (ADisintegrin and aMetalloproteinase) have been strongly implicated in shedding (2Blobel C.P. Cell. 1997; 90: 589-592Abstract Full Text Full Text PDF PubMed Scopus (330) Google Scholar, 3Werb Z. Yan Y. Science. 1998; 282: 1279-1280Crossref PubMed Google Scholar). ADAM17 had been cloned and identified as the TNF-α-converting enzyme (16Black R.A. Rauch C.T. Kozlosky C.J. Peschon J.J. Slack J.L. Wolfson M.F. Castner B.J. Stocking K.L. Reddy P. Srinivasan S. Nelson N. Boiani N. Schooley K.A. Gerhart M. Davis R. Fitzner J.N. Johnson R.S. Paxton R.J. March C.J. Cerretti D.P. Nature. 1997; 385: 729-733Crossref PubMed Scopus (2690) Google Scholar, 17Moss M.L. Jin S.L. Milla M.E. Bickett D.M. Burkhart W. Carter H.L. Chen W.J. Clay W.C. Didsbury J.R. Hassler D. Hoffman C.R. Kost T.A. Lambert M.H. Leesnitzer M.A. McCauley P. McGeehan G. Mitchell J. Moyer M. Pahel G. Rocque W. Overton L.K. Schoenen F. Seaton T. Su J.L. Warner J. Willard D. Becherer J.D. Nature. 1997; 385: 733-736Crossref PubMed Scopus (1476) Google Scholar). Recent studies suggest that ADAM17/TNF-α-converting enzyme cleaves other cell-surface molecules such as interleukin receptor (18Mullberg J. Rauch C.T. Wolfson M.F. Castner B. Fitzner J.N. Otten-Evans C. Mohler K.M. Cosman D. Black R.A. FEBS Lett. 1997; 401: 235-238Crossref PubMed Scopus (55) Google Scholar), β-APP (19Merlos-Suarez A. Fernandez-Larrea J. Reddy P. Baselga J. Arribas J. J. Biol. Chem. 1998; 273: 24955-24962Abstract Full Text Full Text PDF PubMed Scopus (82) Google Scholar),l-selectin, and TGF-α (20Peschon J.J. Slack J.L. Reddy P. Stocking K.L. Sunnarborg S.W. Lee D.C. Russel W.E. Castner B.J. Johnson R.S. Fitzner J.N. Boyce R.W. Nelson N. Kozlosky C.J. Wolfson M.F. Rauch C.T. Cerreti D.P. Paxton R.J. March C.J. Black R.A. Science. 1998; 282: 1281-1284Crossref PubMed Scopus (1359) Google Scholar). Another ADAM family member, MDC9 (ADAM9/Meltrin γ), has been recently shown to be involved in the shedding of HB-EGFTM (21Izumi Y. Hirata M. Hasuwa H. Iwamoto R. Umata T. Miyado K. Tamai Y. Kurisaki T. Sehara-Fujisawa A. Ohno S. Mekada E. EMBO J. 1998; 17: 7260-7272Crossref PubMed Scopus (474) Google Scholar). Protein phosphorylation may be involved in the regulation of shedding. The PMA-induced shedding of TGF-α, β-APP (8Pandiella A. Massague J. J. Biol. Chem. 1991; 266: 5769-5773Abstract Full Text PDF PubMed Google Scholar, 14Arribas J. Coodly L. Vollmer P. Kishimoto T.K. Rose-John S. Massague J. J. Biol. Chem. 1996; 271: 11376-11382Abstract Full Text Full Text PDF PubMed Scopus (359) Google Scholar),l-selectin (22Frey M. Appenheimer M.M. Evans S.S. J. Immunol. 1997; 158: 5424-5434PubMed Google Scholar), TNF-α and its receptors (7Pradines F.A. Raetz C.R. J. Biol. Chem. 1992; 267: 23261-23268Abstract Full Text PDF PubMed Google Scholar, 23Crowe P.D. VanArsdale T.L. Goodwin R.G. Ware C.F. J. Immunol. 1993; 151: 6882-6890PubMed Google Scholar, 24Zhang L. Higuchi M. Totpal K. Chaturvedi M.M. Aggarwal B.B. J. Biol. Chem. 1994; 269: 10270-10279Abstract Full Text PDF PubMed Google Scholar), HER-4/ErbB4 (25Vecchi M. Baulida J. Carpenter G. J. Biol. Chem. 1996; 271: 18989-18995Abstract Full Text Full Text PDF PubMed Scopus (116) Google Scholar), and HB-EGFTM (26Goishi K. Higashiyama S. Klagsbrun M. Nakano N. Umata T. Ishikawa M. Mekada E. Taniguchi N. Mol. Biol. Cell. 1995; 6: 967-980Crossref PubMed Scopus (252) Google Scholar, 27Dethlefsen S.M. Raab G. Moses M.A. Adam R.M. Klagsbrun M. Freeman M.R. J. Biol. Chem. 1998; 69: 143-153Google Scholar) are all inhibited by the relatively nonspecific protein kinase inhibitor staurosporin. Tyrosine phosphorylation (28Slack B.E. Breu J. Petryniak M.A. Srivastava K. Wurtman R.J. J. Biol. Chem. 1995; 270: 8337-8344Abstract Full Text Full Text PDF PubMed Scopus (80) Google Scholar) and phosphatase inhibitors promote shedding. For example, the shedding of β-APP (29Buxbaum J.D. Gandy S.E. Cicchetti P. Ehrlich M.E. Czernik A.J. Fracasso R.P. Ramabhadran T.V. Unterbeck A.J. Greengard P. Proc. Natl. Acad. Sci. U. S. A. 1990; 87: 6003-6006Crossref PubMed Scopus (427) Google Scholar) and TNF-α receptors (30Higuchi M. Aggarwal B.B. J. Biol. Chem. 1993; 268: 5624-5631Abstract Full Text PDF PubMed Google Scholar) is induced by okadaic acid, and the shedding of syndecan-1 (31Reiland J. Ott V.L. Lebakken C.S. Yeaman C. McCarthy J. Rapraeger A.C. Biochem. J. 1996; 319: 39-47Crossref PubMed Scopus (86) Google Scholar), ErbB4/HER-4 and amphiregulin (32Vecchi M. Rudolph-Owen L.A. Brown C.L. Dempsey P.J. Carpenter G. J. Biol. Chem. 1998; 273: 20589-20595Abstract Full Text Full Text PDF PubMed Scopus (82) Google Scholar) is induced by pervanadate. The mechanisms by which PMA induces shedding are still for the most part unknown. To address this question we examined possible mechanisms involved in the PMA-induced shedding of HB-EGF. HB-EGF is a member of the EGF family of growth factors (33Higashiyama S. Abraham J.A. Miller J. Fiddes J.C. Klagsbrun M. Science. 1991; 251: 936-939Crossref PubMed Scopus (1042) Google Scholar) that is synthesized as a membrane-anchored molecule (HB-EGFTM), capable of supporting cell-cell adhesion (34Raab G. Kover K. Paria B.C. Dey S.K. Ezzell R.M. Klagsbrun M. Development. 1996; 122: 637-645Crossref PubMed Google Scholar) and juxtacrine stimulation (26Goishi K. Higashiyama S. Klagsbrun M. Nakano N. Umata T. Ishikawa M. Mekada E. Taniguchi N. Mol. Biol. Cell. 1995; 6: 967-980Crossref PubMed Scopus (252) Google Scholar, 35Higashiyama S. Iwamoto R. Goishi K. Raab G. Taniguchi N. Klagsbrun M. Mekada E. J. Cell Biol. 1995; 128: 929-938Crossref PubMed Scopus (279) Google Scholar). HB-EGFTM is also the receptor for diphtheria toxin (36Naglich J.G. Metherall J.E. Russel D.W. Eidels L. Cell. 1992; 69: 1051-1061Abstract Full Text PDF PubMed Scopus (465) Google Scholar). PMA treatment induces cleavage of HB-EGFTM within 15 min in a number of cell lines (15Suzuki M. Raab G. Moses M.A. Fernandez C.A. Klagsbrun M. J. Biol. Chem. 1997; 272: 31730-31737Abstract Full Text Full Text PDF PubMed Scopus (270) Google Scholar, 26Goishi K. Higashiyama S. Klagsbrun M. Nakano N. Umata T. Ishikawa M. Mekada E. Taniguchi N. Mol. Biol. Cell. 1995; 6: 967-980Crossref PubMed Scopus (252) Google Scholar, 27Dethlefsen S.M. Raab G. Moses M.A. Adam R.M. Klagsbrun M. Freeman M.R. J. Biol. Chem. 1998; 69: 143-153Google Scholar, 37Raab G. Higashiyama S. Hetelekidis S. Abraham J.A. Damm D. Ono M. Klagsbrun M. Biochem. Biophys. Res. Commun. 1994; 204: 592-597Crossref PubMed Scopus (71) Google Scholar). There is a loss of cell-surface associated HB-EGFTM, acquisition of cell resistance to diphtheria toxin (37Raab G. Higashiyama S. Hetelekidis S. Abraham J.A. Damm D. Ono M. Klagsbrun M. Biochem. Biophys. Res. Commun. 1994; 204: 592-597Crossref PubMed Scopus (71) Google Scholar) and release of the mature soluble form of HB-EGF into conditioned medium (CM) (15Suzuki M. Raab G. Moses M.A. Fernandez C.A. Klagsbrun M. J. Biol. Chem. 1997; 272: 31730-31737Abstract Full Text Full Text PDF PubMed Scopus (270) Google Scholar, 27Dethlefsen S.M. Raab G. Moses M.A. Adam R.M. Klagsbrun M. Freeman M.R. J. Biol. Chem. 1998; 69: 143-153Google Scholar, 37Raab G. Higashiyama S. Hetelekidis S. Abraham J.A. Damm D. Ono M. Klagsbrun M. Biochem. Biophys. Res. Commun. 1994; 204: 592-597Crossref PubMed Scopus (71) Google Scholar). Cleavage of HB-EGFTM is inhibited by metalloproteinase inhibitors (15Suzuki M. Raab G. Moses M.A. Fernandez C.A. Klagsbrun M. J. Biol. Chem. 1997; 272: 31730-31737Abstract Full Text Full Text PDF PubMed Scopus (270) Google Scholar,27Dethlefsen S.M. Raab G. Moses M.A. Adam R.M. Klagsbrun M. Freeman M.R. J. Biol. Chem. 1998; 69: 143-153Google Scholar, 38Lanzrein M. Garred O. Olsnes S. Sandvig K. Biochem. J. 1995; 310: 285-289Crossref PubMed Scopus (46) Google Scholar). Mature soluble HB-EGF is a potent stimulator of cell proliferation and migration, for example of smooth muscle cells (SMC), fibroblasts, and keratinocytes (39Raab G. Klagsbrun M. Biochem. Biophys. Acta. 1997; 1333: 179-199PubMed Google Scholar, 40Higashiyama S. Abraham J.A. Klagsbrun M. J. Cell Biol. 1993; 122: 933-940Crossref PubMed Scopus (313) Google Scholar, 41Hashimoto K. Higashiyama S. Asada H. Hashimura E. Kobayashi T. Sudo K. Nakagawa T. Damm D. Yoshikawa K. Taniguchi N. J. Biol. Chem. 1994; 269: 20060-20066Abstract Full Text PDF PubMed Google Scholar). HB-EGF may play a role in SMC hyperplasia (39Raab G. Klagsbrun M. Biochem. Biophys. Acta. 1997; 1333: 179-199PubMed Google Scholar). Its expression is up-regulated in the neointima following balloon injury to rat carotid arteries (42Igura T. Kawata S. Miyagawa J. Inui Y. Tamura S. Fukuda K. Isozaki K. Yamamori K. Taniguchi N. Higashiyama S. Matsuzawa Y. Arterioscler. Thromb. Vasc. Biol. 1996; 16: 1524-1531Crossref PubMed Scopus (59) Google Scholar) and in rat models of pulmonary hypertension (43Powell P.P. Klagsbrun M. Abraham J.A. Jones R.C. Am. J. Pathol. 1993; 143: 784-793PubMed Google Scholar). In addition, it has been detected in medial SMC and in foamy macrophages found in human atherosclerotic plaques (44Miyagawa J. Higashiyama S. Kawata S. Inui Y. Tamura S. Yamamoto K. Nishida M. Nakamura T. Yamashita S. Matsuzawa Y. Taniguchi J. J. Clin. Invest. 1995; 95: 404-411Crossref PubMed Google Scholar). It may be that aberrant shedding of HB-EGF may contribute to these pathologies. Since the conversion of HB-EGFTM to mature soluble HB-EGF has possible physiological and pathological implications, we have further analyzed mechanisms of PMA-induced shedding. In this report we identify several previously unrecognized regulators of HB-EGFTM shedding. These are the Raf-1/MAP kinase cascade and cell adhesion and spreading. All cell culture reagents were purchased from Life Technologies, Inc. Anti-phospho-ERK1/2 antibodies and PD98059 were purchased from Calbiochem. Polyclonal goat anti-ERK1/2, polyclonal rabbit anti-Raf-1, and monoclonal anti-Myc antibodies 9E10 were purchased from Santa Cruz Biotechnology, Inc. (Santa Cruz, CA). Tamoxifen (4-hydroxy) was purchased from Research Biochemicals International (Natick, MA). Fibronectin was purchased from Becton Dickinson (Franklin Lakes, NJ). Heparin-agarose was purchased from Sigma. EZ-link-sulfo-NHS-Biotin was purchased from Pierce. Gamma bind protein G-Sepharose, was purchased from Amersham Pharmacia Biotech. Horseradish peroxidase-conjugated streptavidin, horseradish peroxidase-conjugated anti-rabbit IgG, and CompleteTMmixture of protease inhibitors were purchased from Roche Molecular Biochemicals. Horseradish peroxidase-conjugated anti-mouse IgG was purchased from Promega (Madison, WI). The hydroxamic acid-based metalloproteinase inhibitor, BB3489, was kindly provided by British Biotech (Oxford, UK). Chinese hamster ovary (CHO-K1) cells were purchased from American Type Culture Collection (ATCC, Manassas, VA) and maintained in α-minimal essential medium (α-MEM) supplemented with 10% fetal calf serum, 1% glutamine, 1% penicillin and streptomycin, in 5% CO2. CHO-HB-EGFTMHA/Myc cells were grown to 90–95% confluence in 10-cm dishes (1.8 × 106 cells/dish). HB-EGFTMHA/Myc was constructed so that the hemagglutinin (HA) epitope was inserted in the N-terminal extracellular domain between amino acids Leu83 and Thr85, and the Myc epitope was placed at the C terminus (Fig. 1 A). The doubled-tagged construct was prepared as follows. First HB-EGFTM/myc was prepared by polymerase chain reaction amplification of the complete open reading frame of HB-EGF cDNA (33Higashiyama S. Abraham J.A. Miller J. Fiddes J.C. Klagsbrun M. Science. 1991; 251: 936-939Crossref PubMed Scopus (1042) Google Scholar) using synthetic DNA oligonucleotide primers: a forward primer, 5′-GCTCTAGAGCATGAAGCTGCTGCCGTCG-3′ corresponding to the 5′ end of the full-length HB-EGF open reading frame, and a reverse primer, 5′-GCTCACAGATCCTCTTCTGAGATGAGTTTTTGTTCGTGGGAATTAGTCATGCC-3′, complementary to the nucleotide sequence of a Myc tag followed by the 3′ end of the full-length HB-EGF. The polymerase chain reaction product was ligated into a pCR3.1 mammalian expression vector using the TA cloning kit (Invitrogen, Carlsbad, CA). HB-EGFTM ha/myc was prepared using two complementary oligonucleotides 3′-CCTACCCATACGACGTCCCAGACTACG-5′ and 5′-CGTAGTCGTGGACGTCGTATGGGTAGG-3′ encoding the HA epitope flanked by an MscI site. The oligonucleotides were synthesized and annealed to each other and then inserted into a uniqueMscI site in HB-EGFTM (between amino acids Leu83 and Thr85). The correct sequence of HB-EGFTM ha/myc was confirmed by DNA sequence analysis. For expression, the HB-EGFTM ha/mycinsert was excised from the pCR3.1 vector after an EcoRI digest and subcloned into the EcoRI site of the pIRES/neo mammalian expression vector (CLONTECH, Palo Alto, CA). The resulting plasmid pIRES/neo-HB-EGFTM ha/myc was transfected into CHO-K1 cells using LipofectAMINE and opti-MEM transfection medium (Life Technologies, Inc.) according to the manufacturer's instructions. Twenty four hours post-transfection, cells were passaged 1:25 and plated on 10-cm tissue culture dishes. They were grown in α-MEM supplemented with 10% fetal calf serum, 1% penicillin/streptomycin, and 1 mg/ml G418 in 5% CO2. After 12 days stable clones were selected, expanded, and conditioned media (CM) were collected and tested for the presence of HA-tagged soluble HB-EGF ectodomain by Western blotting with anti-HA antibodies. Five independent clones that overexpressed HB-EGFTMHA/Myc were expanded and characterized. CHO-HB-EGFTMHA/Myc cells were grown overnight to approximately 65% confluence in 10-cm dishes. They were transfected transiently using LipofectAMINE as above with ΔRaf-1:ER plasmid DNA (16 μg/10-cm dish) alone (provided by Dr. Martin McMahon, University of California, San Francisco/Mt. Zion Cancer Center, San Francisco) (45Samuels M.L. Weber M.J. Bishop J.M. McMahon M. Mol. Cell. Biol. 1993; 13: 6241-6252Crossref PubMed Scopus (322) Google Scholar) or co-transfected with HA-ERK1 cDNA (provided by Dr. John Blenis, Harvard Medical School) (46Meloche S. Pages G. Pouyssegur J. Mol. Biol. Cell. 1992; 3: 63-71Crossref PubMed Scopus (131) Google Scholar) and ΔRaf-1:ER cDNA. In co-transfection experiments, the ratio of ΔRaf-1:ER cDNA to HA-ERK1 cDNA was 10-fold. The total amount of cDNA did not exceed 16 μg/10-cm dish. CHO-HB-EGFTMHA/Myc analysis was carried out 22–24 h post-transfection. For stable expression, the ΔRaf-1:ER cDNA construct was transfected into CHO-HB-EGFTMHA/Myc cells as above. Twenty-four hours post-transfection, cells were passaged 1:25 and plated on 10-cm tissue culture dishes. Cells were grown in α-MEM supplemented with 10% fetal calf serum, 1% penicillin/streptomycin, 0.5 mg/ml G418, and 5 μg/ml puromycin (CLONTECH, Palo Alto, CA) in 5% CO2. After 9 days stable clones were selected, expanded, and assayed for activation of MAP kinase in response to tamoxifen. Five independent clones were chosen for further studies. Cells were washed twice with 20 mm Hepes buffer, pH 7.2, 150 mm NaCl (HBS), and incubated on ice with EZ-link-NHS-sulfo-biotin (Pierce, 0.1 mg/ml) in HBS, for 10 min in order to minimize the internalization of cell-surface HB-EGFTM. After aspiration, the cells were washed twice with 20 mm Tris-HCl, pH 7.2, 150 mm NaCl to quench the biotinylation reaction. The cells were washed with HBS, and serum-free α-MEM supplemented with 0.05% BSA (5 ml/plate) was added to cells prior to use. Cells from a 10-cm dish were harvested by scraping into 1 ml of phospho-homogenization buffer that contained 20 mm sodium phosphate, pH 7.2, 50 mm NaCl, 250 mm sucrose, 2 mm EDTA, 0.5 mmsodium orthovanadate, 10 mm NaF, 5 mm sodium pyrophosphate, and a mixture of protease inhibitors (SPH buffer), and then homogenized by passing six times through a 26.5-gauge needle. The nuclei were pelleted by centrifugation at 400 × g. Fractions containing HB-EGFTMHA/Myc were obtained by centrifugation of the post-nuclear supernatants at 15,800 ×g (P2). HB-EGFTMHA/Myc was solubilized by resuspending the P2 pellets in SPH buffer supplemented with Triton X-100 (1% final concentration) and incubating on ice for 10 min. The Triton X-100-insoluble material was pelleted by brief centrifugation at 15,800 × g. Biotinylation studies have shown that virtually all cell-surface HB-EGFTMHA/Myc is contained in P2. Cells grown overnight were washed once with phosphate-buffered saline (PBS) and then detached by incubation with PBS supplemented with 5 mm EDTA for 5 min at 37 °C, 5% CO2. Cells were washed with Hepes-buffered serum-free α-MEM supplemented with 0.1% BSA and resuspended in serum-free medium containing 0.1% BSA. Cells were either maintained in suspension for 30 min or re-plated after 30 min on bacterial dishes precoated with fibronectin at various densities (0–2500 cm2), as described previously (47Ingber D.E. Proc. Natl. Acad. Sci. U. S. A. 1990; 87: 3579-3583Crossref PubMed Scopus (408) Google Scholar). Proteins were resolved on 10 or 15% SDS-PAGE for MAP kinase/ERK or HB-EGF detection, respectively. Proteins were electroblotted for 1.5 h onto a polyvinylidene difluoride membranes (Bio-Rad) in 40 mm CAPS buffer, pH 10.5, in 15% methanol. A constant 24 V was applied. For detection of HB-EGFTMHA/Myc and HB-EGFHA, the membranes were blocked with 3% bovine serum albumin in PBS, 0.25% Tween 20 (PBST). The blots were first incubated with anti-HA or anti-Myc monoclonal antibodies (1:5000) and then with anti-mouse IgG conjugated to horseradish peroxidase (1:5000). For detection of phospho-ERK and total ERKs in the blotting, Tris-buffered saline was substituted for PBS. The blots were incubated with anti-phospho-ERK or anti-ERK1/2 antibodies in (1:2000), followed by anti-rabbit or anti-goat IgG, respectively, conjugated to horseradish peroxidase (1:5000). To detect cell-surface biotinylation after immunoprecipitation with anti-HA, biotinylated proteins were detected using horseradish peroxidase-coupled streptavidin (1:5000). The blots were developed using an enhanced chemiluminescence (ECL) kit according to the manufacturer's instructions (NEN Life Science Products). Cells from a 10-cm dish were scraped into 1 ml of SPH buffer. Triton X-100 was added to 1% final concentration, and the cells were lysed for 20 min on ice. The insoluble material was pelleted by centrifugation at 14,000 ×g at 4 °C for 10 min. Supernatants were precleared by incubation with 40 μl of protein G-Sepharose (50% v/v slurry), for 1 h at 4 °C and incubated overnight with 0.2 μg of the appropriate antibody. The immune complexes were collected by incubating the samples with 40 μl of protein G-Sepharose (50% v/v slurry) for 1.5 h at 4 °C, washed four times with lysis buffer, and boiled in 2× Laemmli's sample buffer. The extent of the PMA-induced HB-EGFTMHA/Myc cleavage and MAP kinase activation was quantified by densitometric scanning of films obtained after ECL using a UMAX PowerLookII scanner and the NIH Image program. The extent of cleavage was calculated by dividing the amount of the intact HB-EGFTMHA/Myc prior to PMA treatment by the amount of intact HB-EGFTMHA/Myc after PMA treatment and corrected for loading. The extent of HB-EGFTM cleavage and MAP kinase activation is expressed in arbitrary units. Cells were transferred a